The role of 11-cis-retinyl esters in vertebrate cone vision - Babino, Darwin (FASEB J, 2015)
A cycle of cis-to-trans isomerization of the chromophore is intrinsic to vertebrate vision where rod and cone photoreceptors mediate dim- and bright-light vision, respectively. Daylight illumination can greatly exceed the rate at which the photoproduct can be recycled back to the chromophore by the canonical visual cycle. Thus, an additional supply pathway(s) must exist to sustain cone-dependent vision. Two-photon microscopy revealed that the eyes of the zebrafish (Danio rerio) contain high levels of 11-cis-retinyl esters (11-REs) within the retinal pigment epithelium. HPLC analyses demonstrate that 11-REs are bleached by bright light and regenerated in the dark. Pharmacologic treatment with all-trans-retinylamine (Ret-NH(2)), a potent and specific inhibitor of the trans-to-cis reisomerization reaction of the canonical visual cycle, impeded the regeneration of 11-REs. Intervention with 11-cis-retinol restored the regeneration of 11-REs in the presence of all-trans-Ret-NH(2). We used the XOPS:mCFP transgenic zebrafish line with a functional cone-only retina to directly demonstrate that this 11-RE cycle is critical to maintain vision under bright-light conditions. Thus, our analyses reveal that a dark-generated pool of 11-REs helps to supply photoreceptors with the chromophore under the varying light conditions present in natural environments.—Babino, D., Perkins, B. D., Kindermann, A., Oberhauser, V., von Lintig, J. The role of 11-cis-retinyl esters in vertebrate cone vision.